Design of a randomized controlled trial of extended-release naltrexone versus daily buprenorphine-naloxone for opioid dependence in Norway (NTX-SBX) - Kunøe, Nikolaj (BMC Pharmacol Toxicol, 2016)
BACKGROUND: Current guidelines for opioid dependence recommend daily maintenance of physical dependence with methadone or buprenorphine, and discourage abstinence due to the high risk of relapse and overdose. Extended-release formulations of the opioid antagonist naltrexone (XR-NTX) block heroin and other opioid agonists competitively for around 4 weeks per administration. XR-NTX thus enables opioid users to experience abstinence from opioid agonists with greatly reduced risk of overdose compared to medication-free abstinence. While XR-NTX has shown promise compared to placebo and daily naltrexone tablets, there is limited information on long-term safety and its performance compared to daily maintenance treatment. METHODS/DESIGN: In this five-hospital RCT with long-term follow-up, we aim to recruit n = 180 patients in treatment for opioid dependence and allocate them in an open, randomized manner (1:1) to receive either 4-week XR-NTX or daily buprenorphine-naloxone (BP-NLX) for the duration of 12 weeks. Allocation is open-label due to the risk of overdose during attempts to self-unmask allocation using heroin. Urine drug tests are scheduled every week with follow-up visits & assessment every 4 weeks. Primary outcomes are abstinence from illicit opioids in urine drug tests and self-report, as well as retention in treatment. Secondary outcomes include other substance use, injecting behavior, drug craving, mental health, quality of life, treatment satisfaction, abstinence motivation, opioid agonist effect rating, insomnia, and pain. Observation is continued for another 36 weeks in order to assess longer-term safety, adherence and effectiveness. The study is an investigator-initiated trial, funded by public grants and approved by an Independent Ethical Committee (the Regional Ethical Committee for Research South-East B # 2011/1320) and the Norwegian Medicines Agency. DISCUSSION: Despite minor implementation problems, the protocol appears sufficiently robust to generate results of high interest to patients, clinicians and policy makers. TRIAL REGISTRATION: Clinicaltrials.gov # NCT01717963, first registered: Oct 28, 2012. Protocol version # 3C, June 12th 2012.